Global Research Trends in the Halal Industry: A Comprehensive Bibliometric Analysis and Visualization - Aulia Normalita (Journal of Halal Review, 2025)
Objective: This study aims to map global research trends in the halal industry, identify the most productive authors, countries, fields of study, and keywords, and highlight research gaps to support future studies. Research Design & Methods: This study uses a bibliometric approach based on data collected from the Scopus database for the period 2010–2025 with keywords such as “halal industry,” “halal economy,” “halal products,” “halal supply chain,” and “halal lifestyle.” The data was analyzed and visualized using VOSviewer software. Findings: The results show that publications related to the halal industry have increased significantly. The development of halal industry research trends based on keywords shows that halal is the most frequently used keyword, followed by the keywords halal industry, halal tourism, halal food, and Malaysia. Malaysia and Indonesia dominate global contributions, making Southeast Asia a leading research center. Implications & Recommendations: These findings suggest the need to strengthen international collaboration, integrate digital technologies such as blockchain into the halal supply chain, and focus on sustainability to ensure a competitive global halal ecosystem. Policymakers should strengthen regulatory frameworks, while researchers can explore interdisciplinary approaches that combine business, technology, and Islamic law. Contribution & Value Added: This study contributes by providing a comprehensive global map of halal industry research trends using VOSviewer, offering new insights into author collaboration networks, thematic evolution, and future research opportunities. This study adds value by identifying emerging topics and providing a strategic roadmap for academics, industry players, and regulators to develop research and practices in the halal industry.